The Potency of Dextranase from Arthrobacter sp. Strain B7 as Dental Plaque Removal - AFAF BAKTIR; NOOR CHOLIES ZAINI; UNTUNG MURDIYATMO; KUNTAMAN KUNTAMAN (Bogor Agricultural University, Indonesia, 2005)
Dextranase of Arthrobacter sp. strain B7 (B7DEX enzyme) was characterized in this study. This enzyme hydrolyzed sucrose and dextran, but not other glucans (starch, nigeran, cellulose, -soluble glucan). It also hydrolyzed glucan from dental plaque with the activity of 7.38 +/- 66 U/ml, where the activity toward dextran was 31.88 +/- 1.24 U/ml. The enzyme exhibited the pH optimum of 7 and the temperature optimum of 50 0C. Its optimum stability was at pH 7 and 50 0C. The enzyme was inhibited by Fe3+, Cu2+, Zn2+, and Ag+, but not by the anionic detergent (SDS) and the nonionic detergent (Triton-X). The enzyme was activated by Ca2+, Na+, Mg2+, and saliva.